The GhmiR157a–GhSPL10 regulatory module controls initial cellular dedifferentiation and callus proliferation in cotton by modulating ethylene-mediated flavonoid biosynthesis. (14th December 2017) - Wang, Lichen; Liu, Nian; Wang, Tianyi; Li, Jianying; Wen, Tianwang; Yang, Xiyan; Lindsey, Keith; Zhang, Xianlong
Abstract : Ethylene-mediated flavonoid biosynthesis is controlled by a GhmiR157 – GhSPL10 regulatory module necessary for initial cellular dedifferentiation and callus proliferation during cotton somatic embryogenesis. Abstract: MicroRNAs (miRNAs) modulate many biological processes through inactivation of specific mRNA targets such as those encoding transcription factors. A delicate spatial/temporal balance between specific miRNAs and their targets is central to achieving the appropriate biological outcomes. Somatic embryogenesis in cotton ( Gossypium hirsutum ), which goes through initial cellular dedifferentiation, callus proliferation, and somatic embryo development, is of great importance for both fundamental research and biotechnological applications. In this study, we characterize the function of the GhmiR157a – GhSPL10 miRNA–transcription factor module during somatic embryogenesis in cotton. We show that overexpression of GhSPL10, a target of GhmiR157a, increases free auxin and ethylene content and expression of associated signaling pathways, activates the flavonoid biosynthesis pathway, and promotes initial cellular dedifferentiation and callus proliferation. Inhibition of expression of the flavonoid synthesis gene F3H in GhSPL10 overexpression lines ( 35S:rSPL10-7 ) blocked callus initiation, while exogenous application of several types of flavonol promoted callus proliferation, associated with cell cycle-related gene expression. Inhibition of ethylene synthesis by aminoethoxyvinylglycine treatment in the 35S:rSPL10-7 line severely inhibited callus initiation, while activation of ethylene signaling through 1-aminocyclopropane 1-carboxylic acid treatment, EIN2 overexpression, or inhibition of the ethylene negative regulator CTR1 by RNA interference promoted flavonoid-related gene expression and flavonol accumulation. These results show that an up-regulation of ethylene signaling and the activation of flavonoid biosynthesis in GhSPL10 overexpression lines were associated with initial cellular dedifferentiation and callus proliferation. Our results demonstrate the importance of a GhmiR157a – GhSPL10 gene module in regulating somatic embryogenesis via hormonal and flavonoid pathways.